The Effect of Entrepreneurship Orientation on Firm Performance: A Multiple Mediation Model. Issue 2 (3rd April 2019) - Jeong, Young-min; Ali, Murad; Zacca, Robert; Park, Kichan
Abstract: Scholars have recognized the important role that entrepreneurial orientation (EO) plays in driving firm performance. However, this relationship is not yet well understood and studies have sought to examine various contingencies that might mediate or moderate this relationship. This study investigates the impact of organization behavior variables on the EO – firm performance relationship. The structural model was tested using primary data from 321 South Korean industrial firms. The results show that EO is positively related to firm performance and that adaptive organizational culture and people-centered management have a multiple mediating effect on the relationship between EO and firm performance.